Produção textual e prática do docente : uma análise no ensino fundamental e médio - Cruz, Vilma Lucia Pereira Silva da (2012)
This study aimed to investigate the practices of teachers of Portuguese related to text production in the public schools, both in the last grades of primary education and in the secondary school, in the city of Escada - PE. This research was grounded in a qualitative approach based on the theoretical contributions of Bronckart (1999), Bakhtin ((1979) 1992, 2000, 2003), Marcuschi (2008), Geraldi (2002), Travaglia (2009), Antunes (2003, 2006, 2009), among others, focusing on issues that approach the use of text production and the practice of correction of this textual production in the context of socio-discursive interactionism. This perspective suggests a language teaching, whose particularities both structural and functional are results of the social environment, mediated by language, contemplating, in this way, new settings for language teaching and a change of attitude of the school in order to work with the language. In order to know the reality that sets the teaching practice about the textual production in primary and secondary education, this research was realized with the analysis of documents referring to the practice of teachers of Portuguese, the analysis of questionnaires answered by the six teachers who are subjects of the research about the theoretical and practical aspects, the analysis of class observations conducted in the classrooms of each participant subject and the interpretative analysis of the practice of correction of texts that were resulted from the lessons observed. It was observed that the work of the subjects with text production shows variations between what they prescribe in their planning, in their responses to questionnaires and their didactic actions, described in the observations records of practical lessons. The results also show that in some practices the teaching action is related to individual procedures, reflected in a traditional formation of language and teaching, focusing on the transmission and reception of knowledge. The results also show relevant evidence in the practice of some teachers, of a work focused on the language education located in the reorientation of focus for the contemplation of their social uses. About the language conception, language and grammar adopted by the subjects and their relations to the theoretical assumptions defended in this research, we also found a significant mismatch in the professional practices related to the two schools surveyed. With regard to the activities implemented by the teachers and their analogy with the theoretical contributions defended in this research, the highlight was the state school, whose theoretical and methodological approaches exhibit the work of language in a socio-interactive perspective, establishing the text as the new linguistic unit, valuing the language in natural and real contexts from the perspective of the socio-discursive interactionism with the practice of textual production. Although confined to a given social reality, the results of this research point to the need to focus efforts on finding new reflections and alternatives to language teaching in the construction of new practices in the classroom